E-Commerce Implementation in An Effort to Consolidate the Competitiveness of Small Industry Businesses - Mukhlis Mukhlis; Andre Jovi Saputra; Deassy Apriani; Taufiq Taufiq (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
Technology brings about changes in all aspects of life, including in business and trade. One of the technologies are presented in business is e-commerce. E-commerce will provide benefits for business actors if utilized optimally, especially for small and medium businesses. This study analyzes the impact of e-commerce implementation efforts to consolidate the competitiveness of small industries in Ogan Ilir Regency. The data used is primary data taken directly by making observations and interviews. Techniques in data retrieval using simple random sampling techniques. The data obtained will be analyzed using statistical analysis and comparative approaches. The results of this study show that the implementation of e-commerce business will have a higher competitiveness index, greater amount of revenue and profit, and more total production, or it can be said that higher productivity than small micro businesses prevent those who have not used ecommerce in their business.